En vurdering af glossematikken og dens reception: Louis Hjelmslevs forudsætninger og fejlgreb - W. Hansen, Erik (Danske Studier, 2024)
In view of the gargantuan and Romantic claims that Louis Hjelmslev concludes Omkring sprogteoriens grundlæggelse with: »we find no non-semiotics that are not components of semiotics (...) and no object (...) is not illuminated from the key position of linguistic theory« and of his wholesale condemnation of the scholarly humanistic tradition of the nineteenth century, one must ask some research ethical questions: what authors did Hjelmslev read? Why did he not discuss the works by scholars to whom the concepts of system, structure, totality, relation, category, deduction, dependence as well as immanence were household theoretical terms long before Hjelmslev (and modern synchronic linguistics) reinvented them? Did he read H. Steffens, J.L. Heiberg, Kierkegaard, Brandes, Høffding, Russell, literary critics like P.V. Rubow and T.S. Eliot? Why did he not discuss the works of his two heroes, Tranekjær-Rasmussen and Jørgen Jørgensen? If Glossematics is to be saved from oblivion and its legacy become a living one, Hjelmslev scholars must doff their obsequiousness and call Hjelmslev’s (epistemological) bluff.